Kate Sanborn correspondence - Sanborn, Kate, 1839-1917.
ALS written by Sanborn to a Miss Churchill, apparently an editor, promising to send her a few paragraphs.
Author, educator, and lecturer. Full name: Katherine Abbott Sanborn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Women authors; Authors; Educators; Lecturers